PENGARUH PENGGUNAAN MEDIA VIDEO KARTUN TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS IX SMP - Riska Amalia; Ramly Ramly; Azis Azis (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
The Effect of Using Media Cartoon Videos Toward The Skill of Writing Short Story for 3rd Year Students of SMP. This study aims to describe:  (1) skill of writing short story for 3rd year students of SMP Negeri 20 Makassar before using media of cartoon videos, (2) skill of writing short story for 3rd year students of SMP Negeri 20 Makassar after using media.of cartoon videos, (3) the effect of using media of cartoon videos toward the skill of writing short story for 3rd year students of SMP Negeri 20 Makassar.  This research is a pre-experimental design research with one-group pretest-posttest design using pretest at the beginning of conducting research  and post test as the final test.  The results of the study found that:  (1) skill of writing short story for 3rd year students of SMP Negeri 20 Makassar before using media of cartoon videos are categorized as less skilled, (2) skill of writing short story for 3rd year students of SMP Negeri 20 Makassar after using media of cartoon videos are categorized as skilled, (3) using media of cartoon videos affect the skill of writing short story for 3rd year students of SMP Negeri 20 Makassar.